Examining the impact of growing household over-indebtedness in China: A corpus linguistics analysis of a popular online debt support forum - Guo, Jiaqi Feng; Marshall, John (Elsevier BV, 2025)
In recent years, Chinese household finances have been reshaped by a massive surge in borrowing. This has seen various financial products including mortgages, consumer loans and credit cards shift from being relatively rare to become central to economic life. Inevitably this is creating ‘over-indebtedness’, where many borrowers cannot repay their obligations. However, in contrast to its scale, there has been little sociological examination of the phenomenon’s impact. This is problematic because, unlike the limited investigation in China, numerous international studies show that over-indebtedness can create significant social harm. To address this research deficit, we undertook corpus analysis of the largest debt support forum on the Chinese internet. While we acknowledge the limitations of online data in this context, the scope of our dataset and the analytical techniques employed, mitigate them to a meaningful extent. Our results suggest borrowers are most concerned about debt collection practices. This includes ‘contact bombing’, where debt collectors attempt to weaponise their social networks by repeatedly calling relatives, friends, and colleagues to pressurise them to repay or face ‘social death’. Discursive patterns indicate the consequences permeate forum members’ lives, distorting their relationships, time horizons and decision-making. Forum discussions also shed light on attitudes to China’s consumer rights framework, with borrowers often reporting a perceived lack of regulatory protection. Alongside its empirical value, the research has important methodological implications. Specifically, few studies have undertaken sociological inquiry in China via corpus analysis of large natural language Mandarin datasets. We provide a showcase for this approach.
Keywords:
Over-indebtedness Debt collection ChinaCorpus linguistics Online forums Contact bombing